PENGARUH ROA, ROE, DAN BOPO TERHADAP HARGA SAHAM BANK UMUM SYARIAH DI INDONESIA - Putri Nabila Larasati; Melia Kusuma (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The research aims to identify and analyze the influence of ROA, ROE, and BOPO to stuck price on share prices in Sharia Commercial Banks in Indonesia for the 2021-2023 period. The population in this study is registered company At Sharia Commercial Bank which consists of 13 Sharia Commercial Banks. The sample of 4 banks taken are Bank Syariah Indonesia, Bank BTPN Syariah, Bank Panin Dubai Syariah, and Bank Aladin Syariah. Sampling was carried out using purposive sampling techniques. method This research nature quantitative namely research which is presented in number form and statistics. Multiple linear regression testing then classical assumption testing was used on testing in this research. Analyze data and test the hypothesis research using software applications 10. The results of this study indicate that the ROA variable partially has a positive but insignificant influence on Stock Prices, ROE has a negative but significant effect on Stock Price, BOPO has a negative but significant influence on Stock Prices, while ROA, ROE, and BOPO simultaneously have a significant influence on stock prices.